Tyrosine Kinase Inhibitor Cabozantinib Inhibits Murine Renal Cancer by Activating Innate and Adaptive Immunity - Liu, Hongyan; Sun, Shishuo; Wang, Gang; Lu, Mengmeng; Zhang, Xiaokang; Wei, Xiaohuan; Gao, Xiaoge; Huang, Chao; Li, Zhen; Zheng, Junnian; Zhang, Qing (Frontiers in Oncology, 2021)
Background: Advanced renal cell carcinoma (RCC) has a very dismal prognosis. Cabozantinib, a tyrosine kinase inhibitor, has been approved for the treatment of advanced RCC. However, the impact of cabozantinib on the immune microenvironment of RCC remains poorly understood. Methods: Kaplan-Meier survival curves were constructed to examine the correlation between intratumor infiltration of neutrophils and patient prognosis in RCC. Infiltration and effector function of neutrophils and T cells in response to cabozantinib treatment were investigated in a murine RCC model. Results: A retrospective study of 307 RCC patients indicated that neutrophils were recruited into tumor tissues, and increased neutrophil infiltration was associated with improved clinical outcomes. In a murine model of RCC, cabozantinib treatment significantly increased both intratumor infiltration and anti-tumor function of neutrophils and T cells. Mechanistically, we found that cabozantinib treatment induced expression of neutrophil-related chemokines (CCL11 and CXCL12) and T cell-related chemokines (CCL8 and CX3CL1) in the tumor microenvironment. Furthermore, depletion of neutrophils and CD8+ T cells compromised the therapeutic efficacy of cabozantinib. Importantly, cabozantinib treatment induced long-term anti-tumor T cell response. Conclusions: Our study revealed novel mechanisms of the therapeutic effects of cabozantinib on RCC by activating both neutrophil-mediated innate immunity and T cell-mediated adaptive immunity. These findings are of great significance for guiding the clinical use of cabozantinib and provide a good candidate for future combination therapy with T-cell therapies or other immunotherapies.